Safe to fail : how resolution will revolutionise banking - Huertas, Thomas F.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Banks are entering a new environment. Regulation and supervision are becoming tougher, so that banks will be less likely to fail. If a bank does fail, bail-in rather than bail-out will be the new resolution regime, so that investors, not taxpayers, bear loss. Safe to Fail sums up the challenges that banks will face and how they can meet them.
Keywords: Science